Professional competences of pre-service teachers: from the F2F to the online learning programme - D'Angelo, Ilaria; Paviotti, Gigliola; Giaconi, Catia; Rodrigues, Maria Beatriz (Form@re - Open Journal per la formazione in rete, 2021)
The COVID-19 pandemic has created significant challenges for the global higher education community: it has required faculty and students to respond to an unprecedented challenge and to shift suddenly from traditional face-to-face curriculum to distance learning formats through virtual classrooms. Some learning programmes, such as the TFA, had a strong theoretical-practical characterisation and were therefore delimited by regulations requiring full in-presence (F2F) and compulsory attendance. Due to the pandemic, the one-year teaching-learning programme for support teachers (TFA) followed the same path and was redesigned by universities for distance education. The re-design at the University of Macerata was based on pedagogical assumptions: technology was intended as a support to achieve learning outcomes. Our study aims to investigate perceptions of the theoretical and practical skills acquired from the F2F and the online format, considering a group of students enrolled for different school orders who followed both the current online programme and the previous years’ F2F programme. Le competenze professionali del docente in formazione: dal corso in presenza al corso online La pandemia da COVID-19 è stata una sfida per la comunità globale dell’istruzione superiore: ha richiesto a docenti e studenti di rispondere a una sfida senza precedenti, e di passare improvvisamente dal curriculum tradizionale in presenza a formati di apprendimento a distanza attraverso aule virtuali. Alcuni percorsi formativi, come il TFA, avevano una forte caratterizzazione teorico-pratica e per questo venivano regolamentati con normative che prevedevano la completa attivazione in presenza e la richiesta di una frequenza obbligatoria. A causa della pandemia, il programma di insegnamento-apprendimento annuale per gli insegnanti di sostegno (TFA) ha seguito lo stesso percorso ed è stato riprogettato dalle università per l’istruzione a distanza. La riprogettazione all’Università di Macerata si è basata su presupposti pedagogici: la tecnologia è stata intesa come supporto per raggiungere i risultati di apprendimento. La nostra indagine indaga le percezioni delle competenze teoriche e pratiche acquisite dal format in presenza e da quello online, considerando un gruppo di studenti che si è trovato nella condizione di seguire il corso attuale in online e quello degli anni precedenti in presenza.